Talk about teaching! : leading professional conversations - Danielson, Charlotte (Thousand Oaks, CA : Corwin Press, a Joint publication with the National Staff Development Council, 2009)
Discusses the importance of professional conversations in improving teaching and learning environments, covering power and leadership in schools, the big ideas that shape professional conversations, topics, conversation skills, and implementation issues, and including conversation activities.
Includes bibliographical references.
Keywords: Teaching; Professional education; Educational leadership